1975
DOI: 10.1136/bjo.59.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical investigation of the subretinal fluid.

Abstract: In the study of the pathogenesis of detachment of the retina an important place is occupied by biochemical research on the subretinal fluid (SRF).According to current theories of pathogenesis, tears are considered to be the main factor in the development of retinal detachment. The Using the same method, Chignell, Carruthers, andRahi (I97i) have demonstrated that the subretinal fluid tends to become more like normal serum the greater the duration of the detachment. However, one of the fractions which is alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…Eyes with a large retinal hole ( \ m=ge\ 1 with RD was 0.06, whereas in human studies, ratios exceeding 1.0 have been encountered.12 This may be due to differences in duration of the detach-ment, the level of vitreous protein, the degree of RPE integrity or transport rate, or retinal hole size. In fellow eyes with vitrectomy alone, mean aqueous and vitreous protein concentrations were 0.28 and 0.23 mg/mL, respectively.…”
mentioning
confidence: 99%
“…Eyes with a large retinal hole ( \ m=ge\ 1 with RD was 0.06, whereas in human studies, ratios exceeding 1.0 have been encountered.12 This may be due to differences in duration of the detach-ment, the level of vitreous protein, the degree of RPE integrity or transport rate, or retinal hole size. In fellow eyes with vitrectomy alone, mean aqueous and vitreous protein concentrations were 0.28 and 0.23 mg/mL, respectively.…”
mentioning
confidence: 99%
“…Sialic acid is one of the major carbohydrates in the glycoproteins and glycolipids of the cellular membranes (Onat et al 1990). Sialic acid has been found in the eye in such places as the trabecular meshwork (Tripathi et al 1987), lens (Tao & Lee 1986), retina (Cohen & Nir 1984), subretinal fluid (Akhmeteli et al 1975), and retinal pigment epithelium (Mclaughlin & Boykins 1987). Rabbit studies demonstrated that the levels of protein, seromucoid, and sialic acid in the aqueous humor correlate with the severity of experimentally induced iridocyclitis (Gieldanowski 1976(Gieldanowski ,1977Szary 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Things appear to be different for SRF crystals. Some researchers suggested a possible correlation between mucopolysaccharide concentration and a surgical outcome [11,12], A previous research on a limited number of cases highlighted a relationship among an unfavourable surgical outcome, high muco polysaccharide concentration and type 3 crys tallization [13], Nevertheless, it is well known that the SRF ferning test is mainly influenced by protein level [14], Therefore, more extensive investigations are required in order to demonstrate the pos sible relationship between the SRF ferning test and a surgical outcome. If this hypothesis could be verified, fractal dimension analysis would become very useful for the determina tion of crystallization morphology, hence for surgical prognosis.…”
Section: Discussionmentioning
confidence: 99%